Renin-Angiotensin-Aldosterone System Inhibitors in Patients with Covid-19 - Feldman, Andre; Arruda, Guilherme D’Andréa Saba; Ferreira de Souza, Olga (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
COVID-19 is a new disease caused by the Sars-CoV-2 virus and the vast majority of patients have symptoms similar to a flu-like syndrome. A small portion of those infected ends up being hospitalized and may develop with the most severe presentation of the disease. Data from Chinese series report that hypertension appears to be a condition that imposes a greater risk of unfavorable evolution of patients. Some studies have reported that Sars-CoV-2 uses the angiotensin-converting enzyme to access its target cells. There are theories that differ about the protective or harmful role that drugs that act in the renin angiotensin aldosterone system in these patients. A British study suggests that patients using angiotensin-converting enzyme inhibitors had a lower incidence of severe forms of the disease. Another study carried out a retrospective and multicenter analysis showing that mortality was lower in the group that had used the drugs when compared to the other group (3,7 vs. 9,8%; p=0,01). The various hypotheses raised through pathophysiology are not yet able to really predict the best course of action for patients using drugs that act on the renin angiotensin system. Thus, a randomized study becomes important to try to answer definitively and with a high degree of reliability to this question.